Critical analysis of the benefits and drawbacks of assistive technology with special needs - Alshabeb, Abdulrahman M.; Alharbi, Omran (Advances in Social Sciences Research Journal, 2019)
Assistive technology has emerged as powerful platforms in education field. Assistive technology is helping disabled individuals in a big manner. Increasing computer-based technology has created a sea change for all the disabled students. It has ended the isolation or limited opportunities which disable students have faced for so long. Assistive technology has been designed or created to make it easier for disabled learners for accessing material, communicating their work or ideas and participating in different educational programs. All these technologies help many of those students who are not able to see, hear, walk and talk. The development of modern special education is the advent of adaptive and assistive technologies which gets used by the teachers to help the students for achieving the good learning at possible levels. For becoming a culturally responsible person, it is very important to achieve success in the globalized or modern world. This article is attempt to discuss the benefits and drawbacks of assistive technology with special needs.